Diverse GUI Interaction Logs Enhance Generalization in GUI Agents Across Unseen Domains - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: What is the impact of including diverse GUI interaction logs in the fine-tuning dataset on the macro-averaged success rate of GUI agents across unseen domains in the AppSight benchmark. 6 claims were extracted from source literature; 6 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.7/10. This report is a machine-g
Machine-generated literature synthesis.